RAQAMLI TEXNOLOGIYALAR ASOSIDA: QISHLOQ XO‘JALIGI KLASTERLARI RESURSLARINI SAMARALI BOSHQARISHNING ZAMONAVIY KONSEPSIYASI SIFATIDA LEAN TEXNOLOGIYASI - Shaynazorov Alisher; Turabeyeva K (TADQIQOTLAR.UZ, 2024)
The article reveals the role of the Lean Production concept, based on digital thexonologies, one of the modern concepts for the organization of processing of clusters agricultural products, in the effective management of the resources of agricultural clusters, as well as proposals for its introduction. The theory and views on”Lean Production " were analyzed and its elements fully covered.